Analisa Penataan Outlet Channel Sungai Karang Anyar Di Kota Tarakan - Irianto, Danang Bimo; Sisinggih, Dian; Priyantoro, Dwi (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2014)
Karang Anyar outlet channel has the outlets that directly flow in to the sea and it’s influenced by the tides. Flooding often occurs when rain along with high tides. The outlet channel has a very gentle slope,initial data mentioned that outlet channel length is approximately 1625 m, elevation in the upstream = +4.40 m and +0.10 m in the downstream, with an average slope = 0.003. Elevation embankment upstream = +6.00 m and downstream = +1.50 m. Meanwhile, according to secondary data, the flood with 10 th years return periode that flow in the outlet channel is 66.4 m 3 /sec and the flood with 25 th years return periode is 75.16 m 3/sec. On average, a tide water level is +1.5 m above sea level. Based on the variety of modeling, the action concepts that can eliminate the flooding are these following action: widening the channel dimension, build the embankment on channel side, making the local storage for each sub-catchment in the downstream, making the gate for the local storage, making tidal gate to prevent the tide come into the system, making the retarding basin to accommodate flood waters from upstream when the outlet is closed due to high tide.Keyword: Outlet channel, Regional arrangement, Outlet, Karang Anyar, Tarakan